Pelatihan Berbusana Jawa Gagrag Ngayogyakarta bagi Pelajar: Upaya Meluruskan Pemahaman dan Keterampilan Berbusana Adat - Purbosari, Riris; Nadzari, Puput Fatikhah; Ningrum, Dela Octavia; Handayani, Wuri; Sari, Gita Indah; Saputra, Nur Ahmad; Yoni, Aisa; Munif, Muhammad Robiul; Nurhayati, Endang (Bahasa Indonesia, 2025)
The training on Javanese attire of the Ngayogyakarta style serves as a response to students’ mistakes in practicing the proper way of dressing in the Ngayogyakarta Javanese style during Thursday Pon at schools in the Special Region of Yogyakarta. The aim of implementing the training is to correct and improve the understanding and skills of training participants who are middle school and high school students in wearing Ngayogyakarta Javanese style clothing. The training was held in Bangunrejo Hamlet, Merdikorejo Village, Tempel District, Sleman Regency, Special Region of Yogyakarta. This training was organized by students of Javanese Language B Professional Teacher Education for Prospective Teachers, Yogyakarta State University. The method used in this activity is Service Learning (SL). There are four stages of activities, namely planning, implementation, monitoring and evaluation. There are four main points of discussion in this article, namely the socialization of Ngayogyakarta style Javanese fashion, the practice of tying techniques for Ngayogyakarta style fabric, the practice of wearing Javanese Ngayogyakarta style clothing, and the training participants' achievements in understanding the material. Based on the pretest and posttest conducted before and after the training, this program was able to correct and improve the participants’ understanding of Javanese fashion in Ngayogyakarta style. The participants’ skills also improved, namely in draping and dressing in Ngayogyakarta Javanese fashion properly and correctly. Sustainability of the program is carried out through monitoring the consistency and development of the Javanese Ngayogyakarta style of dress by students during Thursday Pon or other activities by program organizers who are part of the community and educators.   Abstrak Pelatihan berbusana Jawa gagrag Ngayogyakarta merupakan bentuk tanggapan terhadap kesalahan penggunaan busana Jawa gagrag Ngayogyakarta oleh peserta didik pada Kamis Pon di sekolah-sekolah wilayah Daerah Istimewa Yogyakarta. Tujuan pelaksanaan pelatihan adalah meluruskan dan meningkatkan pemahaman dan keterampilan peserta pelatihan yang merupakan peserta didik SMP dan SMA dalam berbusana Jawa gagrag Ngayogyakarta. Pelatihan dilaksanakan di Dusun Bangunrejo, Kelurahan Merdikorejo, Kecamatan Tempel, Kabupaten Sleman, Daerah Istimewa Yogyakarta. Pelatihan ini diselenggarakan oleh mahasiswa Pendidikan Profesi Guru bagi Calon Guru Bahasa Jawa B Universitas Negeri Yogyakarta. Metode yang digunakan dalam kegiatan ini adalah Service Learning (SL). Terdapat empat tahapan kegiatan, yakni perencanaan, pelaksanaan, pemantauan, dan evaluasi. Terdapat empat pokok bahasan dalam artikel ini, yakni sosialisasi busana Jawa gagrag Ngayogyakarta, praktik mewiru jarik gagrag Ngayogyakarta, praktik berbusana Jawa gagrag Ngayogyakarta, dan ketercapaian peserta pelatihan dalam memahami materi. Berdasarkan pretest dan posttest yang dilaksanakan sebelum dan setelah pelatihan, pelatihan ini dapat meluruskan dan meningkatkan pemahaman peserta pelatihan dalam hal busana Jawa gagrag Ngayogyakarta. Keterampilan peserta pelatihan juga bertambah, yakni terkait keterampilan mewiru dan berbusana Jawa gagrag Ngayogyakarta dengan baik dan benar. Keberlanjutan program dilaksanakan melalui pemantauan konsistensi dan perkembangan cara berbusana Jawa gagrag Ngayogyakarta oleh peserta didik ketika Kamis Pon atau kegiatan lainnya oleh penyelenggara program yang merupakan bagian dari masyarakat dan pendidik.